Discretionary Behavior with Respect to the Adoption of Sfas 142 and the Behavior of Security Prices - Zang, Yoonseok (Institutional Knowledge at Singapore Management University, 2004)
In June 2001, the Financial Accounting Standards Board (FASB) issued SFAS 142, Goodwill and Other Intangible Assets, which takes a very different approach to how goodwill is accounted for subsequent to the initial recognition. The new statement requires that goodwill no longer be amortized, but instead requires a transitional goodwill impairment (initial impairment loss or IIL) test in the adoption fiscal year and an annual impairment test thereafter. Since SFAS 142 allows firms substantial judgment in the adoption year in determining the amount of impairment loss, this dissertation first examines management discretionary behavior in measuring the IIL. The result shows that the IIL charge is greater in magnitude when there has been recent management turnover and is smaller for firms that are more highly leveraged, controlling for the economic impairment loss. These results provide support for the contention that the IIL is used to manage earnings. Second, this dissertation investigates if firms' stock prices respond to the IIL charge and the boost in earnings due to the elimination of goodwill amortization. Ex ante , I predict that an unanticipated IIL charge will have a negative impact on the firm's stock price, and predict no reaction to the exclusion of amortization. As hypothesized, there was no significant price reaction to the elimination of amortization. However, the market responded negatively to the unanticipated IIL, with the reaction stronger for highly leveraged firms. Further analysis shows that subsequent to the IIL announcement, analysts revised their upcoming quarters' earnings forecasts downward in response to the unanticipated IIL. I interpret these results as evidence that the unexpected IIL conveys value-relevant information about a negative view of future profit-making potential and/or adverse impact on firms' debt contracts. The results of this dissertation will help us better understand the importance of managers' incentives in determining the goodwill impairment charge as well as the information content and shareholder wealth effects of the announcement of the IIL charge and the exclusion of amortization.